Effects of Climbing on Core Strength and Mobility in Adults - Muehlbauer, T.; Stuerchler, M.; Granacher, U. (International Journal of Sports Medicine, 2012)
The objective of this study was to examine the impact of an indoor climbing training and detraining program on core/handgrip strength and trunk mobility in men and women. 28 young sedentary adults participated in this study and were assigned to an intervention (30±3 years) or a control (29±2 years) group. The intervention group participated in 8 weeks (2 times/week) of indoor climbing training, followed by 8 weeks of detraining. Tests included the measurement of maximal isometric strength (MIS) of the trunk flexors/extensors, the assessment of trunk mobility in the sagittal (SAP) and the coronal (CRP) plane as well as testing of handgrip strength. After training, significant improvements were observed in MIS of the trunk flexors/extensors (~19–22%, all p<0.01), in trunk mobility in SAP/CRP (~14–19%, all p<0.01), and in handgrip strength (~5%, p<0.01). During detraining, MIS (~12–13%, all p<0.01) and trunk mobility (~7–10%, all p<0.01) deteriorated significantly, whereas handgrip strength remained. This indoor climbing training program conducted in sedentary adults proved to be feasible (i. e., attendance rate of 89.4%) and effective. It is suggested that indoor climbing should be permanently conducted to maintain the observed improvements in core muscle strength and trunk mobility.
Keywords: intervention; detraining; young adults; sedentary